The production of English syllable-level timing patterns by bilingual English- and Spanish-speaking children with cochlear implants and their peers with normal hearing. (November 2022) - Gibson, Mark; Bunta, Ferenc; Johnson, Charles; Huárriz, Miriam
Highlights: We addressed the production of syllable-level timing parameters in stop+sonorant clusters by bilingual English- and Spanish-speaking children. The results of the English production tasks show effects of syllable complexity on VOT, whereby VOT for word initial singleton stops was shorter than VOT in stop+sonorant clusters. A lengthening effect was found for vowel duration, where vowels tend to extend temporally as more consonants are added to the onset. For lateral and rhotic duration in word initial singleton and complex onsets, both groups (CImp and NH) showed the typical compression effect of /l/ in complex onsets characteristic of English syllable timing, though no shortening of the rhotic was found in complex onsets for the NH group. Abstract: We examined the timing parameters in syllables of English containing word initial singleton sonorants (/l/ and /ɹ/) and stop+sonorant clusters by bilingual English- and Spanish-speaking children with cochlear implants (CImp group) and their cohorts with normal hearing (NH group). The timing parameters included: voice onset time (henceforth, VOT), vowel duration following word initial singleton consonants and vowels following word initial stop+sonorant clusters as well as lateral and rhotic duration in word initial position and in stop+sonorant clusters. Our motivation for the current study was to address whether hearing loss affects the production of the timing parameters of syllables and whether language interference in bilingual productions is modulated by hearing loss. The results of the English production tasks show effects of onset type (singleton, C, vs complex onsets, CC) on VOT, whereby VOT for word initial singleton stops was shorter than VOT in stop+sonorant clusters. To the contrary vowel duration tended to extend temporally as more consonants are added to the onset. With regard to lateral and rhotic duration in word initial singleton and complex onsets, both groups (CImp and NH) showed the typical compression effect of /l/ in complex onsets characteristic of the timing pattern for sonorants in English complex syllables, though no shortening of the rhotic was found for the NH group. Combined results suggest little effect of hearing loss on the production of the timing parameters of English syllables, and virtually no effects across groups that can be attributed to language interference.